The Nature of Project Management in South African SMEs: A Look at Insurtech in the Western Cape Province of South Africa - Antonio, Wilton (Department of Construction Economics and Management, 2023)
Background: Project management is essential for organisations, especially for achieving goals and creating value. However, the literature on project management is biased towards large enterprises (LEs), which differ fundamentally from small to medium enterprises (SMEs) in their structures, processes, procedures, and characteristics. Thus, SMEs have different project management needs, which the literature barely addresses. Given the importance of SMEs in economic development, job creation, and innovation, a growing area of research is aiming to develop simpler versions of project management for SMEs. A significant part of this development is understanding the nature of project management in SMEs. However, most studies explore American, Australian and European SMEs; none explore South African SMEs. Objectives: This study investigates the nature of project management in South African SMEs - to contribute to the growing area of research. Methodology: This study began a literature review - focusing on SMEs and their characteristics, project management concepts, project management in SMEs, and an overview of the fintech landscape. Using case research, semi-structured interviews, and thematic analysis, four insurtech SMEs in the Western Cape province of South Africa were investigated. The investigation looked at how they perceived and understood project management, the factors to its adoption and utilisation, its benefits and drawbacks, and how they practised it. Results: The results show that SMEs had a positive perception of project management and its necessity; however, they only identified the short-term, internal values. The factors affecting project management adoption and utilisation in SMEs were: active ownermanager involvement, corporate culture and flat organisational structure, education and experience, the desire for workplace flexibility, and smaller project sizes. Overall, the SMEs had simpler, less formal practices and lacked formal project managers. Their practices firmly focused on planning, emphasising collecting requirements, breaking down the work, and compiling the schedule. Monitoring and control practices were the second most common (after planning), emphasising monitoring the scope and schedule. Other practices in the initiation, execution and closing process groups were not common – only the larger SME had practices in these process groups. Findings: The findings in this study agree with the literature, which shows that SMEs have simpler, less formal project management practices. Moreover, larger SMEs tend to have more formal processes compared to smaller SMEs. Conclusion: South African SMEs have simpler, less formal project management practices that ownermanagers highly influence. Moreover, SMEs typically do not have formal project managers. Therefore, simpler versions of project management need to account for these factors.